2015
DOI: 10.3390/medicines2030212
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diabetic Gastroparesis by Complementary and Alternative Medicines

Abstract: Gastroparesis is a common gastrointestinal complication in diabetes, induced by hyperglycemia and characterized by delayed gastric emptying and upper abdominal symptoms, such asnausea, vomiting, early satiety, bloating and epigastric pain. Diabetic gastroparesis (DGP) affects life quality and glycemic control, and is a challenge to treat in both Western and Eastern medicine. Routine treatment in Western medicine includes gastric emptying promoted by prokinetic agents, gastric pacemaking, or surgery combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…However, adherence to long-term treatment is difficult because of the side effects of drugs, and the effect is always unsatisfactory. [67]…”
Section: Discussionmentioning
confidence: 99%
“…However, adherence to long-term treatment is difficult because of the side effects of drugs, and the effect is always unsatisfactory. [67]…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been used to manage a variety of gastrointestinal problems, including irritable gastroparesis, irritable bowel syndrome (IBS), acute pancreatitis, and more. Gastroparesis is characterized by delayed gastric emptying with associated upper abdominal symptoms and is often a complication of diabetes-induced hyperglycemia or surgery ( 56 ). A systematic review of acupuncture for the treatment of gastroparesis found preliminary qualitative evidence that acupuncture provided short-term improvement in symptoms of gastroparesis, regardless of etiology (i.e., diabetes, surgery) ( 57 ).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…Попри активне впровадження методів рефлексотерапії для корекції М-ЕФ шлунку у хворих на ЦД 1-го типу застосування викликає багато дискусій у зв'язку з відсутністю достатньої доказової бази: результати восьми міжнародних багатоцентрових досліджень із загальною кількістю обстежених 585 хворих на ЦД доведено ефективність сеансів акупунктури при уповільненні моторики шлунку, так як сприяють збудженню блукаючого нерва і гальмуванню симпатичних нервових закінчень. У літературі з'являються все більше даних, які доводять необхідність ширшого впровадження у щоденну медичну практику нових лікувальних комплексів [6][7][8].…”
Section: обґрунтування дослідженняunclassified
“…Аналіз отриманих нами даних, свідчать, що сеанси акупунктури є швидкодіючими, ефективними і безпечними для пацієнтів хворих на ЦД 1-го типу та ознаками уповільнення М-ЕФ шлунку. Крім того, слід вказати на низку переваг даного лікувального комплексу, що дозволяє ефективно запобігти прогресування симптомів дизмоторики шлунку, економічно вигідніший від прийому великої кількості препаратів медикаментозної терапії, а також відсутній токсичний вплив хімічних середників [5,7].…”
Section: обговорення результатів дослідженняunclassified